Novel soliton solutions to the Atangana-Baleanu fractional system of equations for the ISALWs - Asjad Muhammad Imran; Ullah Naeem; Rehman Hamood Ur; Gia Tuan Nguyen (DE GRUYTER POLAND SP Z O O, 2022)
This work deals the construction of novel soliton solutions to the Atangana-Baleanu (AB) fractional system of equations for the ion sound and Langmuir waves by using Sardar-subequation method (SSM). The outcomes are in the form of bright, singular, dark and combo soliton solutions. These solutions have wide applications in the arena of optoelectronics and wave propagation. The bright solitons will be a vast advantage in controlling the soliton disorder, dark solitons are also beneficial for soliton communication when a background wave exists and singular solitons only elaborate the shape of solitons and show a total spectrum of soliton solutions created from the model. These results would be very helpful to study and understand the physical phenomena in nonlinear optics. The performance of the SSM shows that this is powerful, talented, suitable and direct technique to discover the exact solutions for a number of nonlinear fractional models.